Globalization and inequalities. Complexity and contested modernities - Walby, Sylvia (London, 2009)
"This groundbreaking book places globalisation, difference and gender at the heart of social theory, and demonstrates the powerful capacity of complexity theory to enable innovative social analysis. The author challenges social theory to incorporate gender and other forms of difference and inequality, rejecting the practice of treating gender as a separate category of analysis and demonstrates the relevance of gender and difference for central issues in contemporary social theory and analysis."